"The Role of the Islamic Education Teachers in Promoting Citizenship Values and Belonging from the Perspective of Secondary School Students in AL- Qunetira Governorate" (Damascus University Journal of educational and Psychologyical sciences, 2025)
The idea of citizenship and the extent to which its values are promoted in the minds of the new generation is one of the important and necessary topics in individual and societal life. Recently, it has become a pressing need due to the many confusions and misguided currents that have swept our country, and some people lack an understanding of the concept of citizenship and its values, which are a strong barrier for protecting the homeland. Therefore, this study aims to shed light on the role of Islamic education teachers in promoting citizenship values among secondary school students in Al- Quneitra governorate as an. This study used a descriptive approach, with a study population consisting of secondary school students in Al- Quneitra governorate. The sample consisted of 150 students, randomly selected from their schools, and a questionnaire was used as a research tool. The results showed that the level of promotion of citizenship values by Islamic education teachers among secondary school students in Al- Quneitra governorate was high, with an average score of 3.41. The results also indicated that there was no statistically significant difference between the average of Islamic education teachers' responses on the level of promotion of citizenship values among secondary school students in Al- Quneitra governorate according to the class variable, and there were statistically significant differences according to gender and specialization variables.
Keywords: Role; Promoting; Teacher; Secondary School; The Islamic Education; Citizenship; Belonging